Green‐Sensitive Phototransistor Based on Solution‐Processed 2D n‐Type Organic Single Crystal. (23rd July 2019) - Kim, Jin Hong; Oh, Sangyoon; Park, Sang Kyu; Park, Soo Young
Abstract: 2D single crystals of down to two‐monolayer thickness are fabricated from a push–pull structure‐based green light absorbing organic n‐type semiconductor, (2 E, 2′ E )‐3, 3′‐(2, 5‐difluoro‐1, 4‐phenylene)bis(2‐(5‐(4‐(trifluoromethyl)phenyl)thiophen‐2‐yl)acrylonitrile) (2F‐4‐TFPTA). The 2F‐4‐TFPTA 2D single crystal exhibits field‐effect electron mobility of 0.9 cm 2 V −1 s −1 in the dark and also decent photoresponsivity of 3.6 × 10 3 A W −1 under green light‐emitting diode irradiation, which is noted as the first demonstration of green‐sensitive 2D organic phototransistors. Photoresponse time of this 2F‐4‐TFPTA 2D single‐crystal device is as fast as 43 ms for the rise and 85 ms for the decay. Abstract : A green‐absorbing organic 2D crystal as an image sensor is reported. (2 E, 2′ E )‐3, 3′‐(2, 5‐Difluoro‐1, 4‐phenylene)bis(2‐(5‐(4‐(trifluoromethyl)phenyl)thiophen‐2‐yl)acrylonitrile) (2F‐4‐TFPTA) exhibits absorption at 518 and 543 nm. 2F‐4‐TFPTA forms bilayer‐thick single crystals directly on substrates by solution‐processed self‐assembly. The phototransistor exhibits maximum electron mobility of 0.9 cm 2 V −1 s −1 under dark and photoresponsivity of up to 3.6 × 10 3 A W −1 under green light irradiation.